2023
DOI: 10.1161/jaha.122.028939
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Azithromycin and Cardiovascular Outcomes in Unvaccinated Patients With COVID‐19 and Preexisting Cardiovascular Disease

Abstract: Background Empiric antimicrobial therapy with azithromycin is highly used in patients admitted to the hospital with COVID‐19, despite prior research suggesting that azithromycin may be associated with increased risk of cardiovascular events. Methods and Results This study was conducted using data from the ISACS‐COVID‐19 (International Survey of Acute Coronavirus Syndromes‐COVID‐19) registry. Patients with a confirmed diagnosis of SARS‐CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Two hundred-three studies were excluded because they did not report data on antibiotic use in COVID-19 patients. Of the remaining 77 studies, 29 studies were included in this systematic review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two hundred-three studies were excluded because they did not report data on antibiotic use in COVID-19 patients. Of the remaining 77 studies, 29 studies were included in this systematic review [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 29 studies included in the systematic review, 18 studies were on the prevalence of bacterial infection and antibiotics use in hospitalized COVID-19 patients [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; of these studies, 5 reported on patients admitted to the intensive care unit [ 20 , 21 , 22 , 23 , 24 ]. Four studies reported on the efficacy of early antibiotic use in hospitalized COVID-19 patients [ 25 , 26 , 27 , 28 ]; four studies were on the use of sepsis biomarkers to improve antibiotic use among COVID-19 patients [ 29 , 30 , 31 , 32 ]; three studies were on the efficacy of antimicrobial stewardship programs and predictive models among COVID-19 hospitalized patients [ 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations